2012
DOI: 10.3390/molecules17088917
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotection of Suaveolol, Isolated from Hyptis suaveolens, against Ethanol-Induced Gastric Lesions in Wistar Rats: Role of Prostaglandins, Nitric Oxide and Sulfhydryls

Abstract: Hyptis suaveolens is a medicinal plant that is, according to traditional medicine, considered useful in the treatment of gastric ulcers. Although its gastroprotective activity was reported, the active compounds have not been identified. Therefore, the aim of the present study was to identify at least one active compound potentially responsible for the gastroprotective activity of H. suaveolens by using a bioassay guided study with an ethanol-induced gastric ulcer experimental model in rats. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
4
12
0
2
Order By: Relevance
“…The antioxidant activity of the pre-treatment with the zinc (II) complex was increased in the gastric homogenates similar to the antioxidant activities of the reference medicine [72]. This study in consistence with several studies showed that antioxidant property was one of the main gastroprotective mechanisms [29], [33], [42], [53]. The Zn (II) complex appeared effective in the mid doses (2.181×10 −5 and 4.362×10 −5 M/kg).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The antioxidant activity of the pre-treatment with the zinc (II) complex was increased in the gastric homogenates similar to the antioxidant activities of the reference medicine [72]. This study in consistence with several studies showed that antioxidant property was one of the main gastroprotective mechanisms [29], [33], [42], [53]. The Zn (II) complex appeared effective in the mid doses (2.181×10 −5 and 4.362×10 −5 M/kg).…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have promoted ethanol-induced model of hemorrhagic gastric lesions [34], [51][53]. It has been established that one of the most important detrimental effects evoked by ethanol-induced gastric lesion is represented by increments of gastric mucosal MDA levels, a marker for oxidative stress [54].…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22] The gastroprotective activity of terpenes of various skeletal types under different experimental conditions has been reported in the literature but showed significant activity only at a single oral dose of 100 mg/kg. [19][20][21][22][23] In a previous study, we found a gastroprotective effect of some of the ferruginol derivatives tested that was comparable with the Azorella diterpenoids reported here under the same experimental conditions (20 mg/kg). [24] However, in comparison with poligodial, carnosol, 6,7-royleanone, 7,20epoxiroyleanone, royleanone and horminone, under the same the conditions, the gastroprotective effect of Azorella diterpenes is lower.…”
Section: Discussionsupporting
confidence: 68%
“…However, all of these drugs are associated with undesirable side effects, making the development of alternative treatments necessary. In this context, medicinal plants provide an important source of new chemical substances with potential therapeutic effects (Vera-Arzave et al, 2012). In traditional medicine of the state of Chiapas, Mexico, Peperomia hispidula (Piperaceae), locally known as lenteja, is commonly prepared as an infusion and used to treat gastric ulcers.…”
Section: Introductionmentioning
confidence: 99%